HAZOR EB III CITY ABANDONMENT AND IBA PEOPLE RETURN: RADIOCARBON CHRONOLOGY AND ITS IMPLICATIONS. Issue 5 (14th October 2021) - Lev, Ron; Bechar, Shlomit; Boaretto, Elisabetta
ABSTRACT: Tel Hazor is one of only a few sites in Israel where remains of the Intermediate Bronze Age (IBA) in the second half of the 3rd millennium BC were found on top of Early Bronze III (EB III) city remains. A probe excavation was held at Hazor in 2017 to explore the chronological relation between the EB III and the IBA occupation. The radiocarbon ( 14 C) absolute dates generated from this probe excavation show that following the EB III city demise, the site was abandoned for up to a few hundred years before it was resettled in the IBA. 14 C dates obtained from the last level of the EB III city are well before 2500 BCE, fully aligned with the recent "High Chronology" for the EBA in the southern Levant. The excavation also produced dates associated with IBA "Black Wheel-Made Ware" vessels, which were found in large numbers at Hazor.